Evaluation of gonadotropin-replacement therapy in male patients with hypogonadotropic hypogonadism - Mazhar Ortac; Muhammed Hidir; Emre Salabas; Abubekir Boyuk; Caner Bese; Yasar Pazir; Ates Kadioglu (Asian Journal of Andrology, 2019)
Hypogonadotropic hypogonadism (HH) is a rare disease in which medical treatment has a high success rate to achieve fertility. This study aimed to analyze the efficacy of hormone replacement therapy and determine predictive factors for successful spermatogenesis and spontaneous pregnancy in patients with idiopathic HH. A total of 112 patients with low testosterone (T), luteinizing hormone (LH) and follicle-stimulating hormone (FSH), and normal prolactin levels were diagnosed with HH and administered LH and FSH analogs as hormone replacement therapy. During treatment, 96 (85.7%) patients had sperm present in ejaculate samples. Among these patients, 72 were married and wanted a child. Of these 72 patients, 48 (66.7%) of couples had pregnancies from natural conception. After initiation of treatment, the mean time for the appearance of sperm in semen was 9.48 months. There were no significant differences between baseline FSH, T, and LH levels; however, older age, larger testicular size, and low rate of undescended testes were favorable factors for successful spermatogenesis. Larger testicular size and older age were also the main predictive factors for natural conception. We found that patients with undescended testes had a younger age, smaller testes, and lower T levels compared with patients exhibiting descended testes. The rate of sperm found in the ejaculate was not significantly decreased in patients with undescended compared with descended testis (73.7% vs 87.6%, P = 0.261). The medical approach for males with HH and azoospermia provides a successful treatment modality in regard to successful spermatogenesis and achievement of pregnancy.